2022
DOI: 10.1371/journal.pone.0261679
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing in COVID-19 patients identifies neutrophil activation biomarkers as a promising diagnostic platform for infections

Abstract: Infection with the SARS-CoV2 virus can vary from asymptomatic, or flu-like with moderate disease, up to critically severe. Severe disease, termed COVID-19, involves acute respiratory deterioration that is frequently fatal. To understand the highly variable presentation, and identify biomarkers for disease severity, blood RNA from COVID-19 patient in an intensive care unit was analyzed by whole transcriptome RNA sequencing. Both SARS-CoV2 infection and the severity of COVID-19 syndrome were associated with up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…CCR5 was downstream TGs in this regulatory network, and it encoded a protein on the surface of white blood cells that is involved in the immune system 29 . We found that 2 TGs (CCR5, CXCR6) of the 15 immune TGs were also differentially expressed in blood samples of fatal COVID-19 patients 30 ( 𝑃 ≤ 0.014 ), which supported that our reconstructed sub-regulatory networks of immune cells were significantly associated with severity of COVID-19. In COVID-19 severity associated epithelium regulatory network, there were totally 16 TFs, 24 REs and 10 TGs associated with 42 SNPs (Figure 2B).…”
Section: Construction Of Snp Associated Regulatory Network Of Immune ...supporting
confidence: 75%
“…CCR5 was downstream TGs in this regulatory network, and it encoded a protein on the surface of white blood cells that is involved in the immune system 29 . We found that 2 TGs (CCR5, CXCR6) of the 15 immune TGs were also differentially expressed in blood samples of fatal COVID-19 patients 30 ( 𝑃 ≤ 0.014 ), which supported that our reconstructed sub-regulatory networks of immune cells were significantly associated with severity of COVID-19. In COVID-19 severity associated epithelium regulatory network, there were totally 16 TFs, 24 REs and 10 TGs associated with 42 SNPs (Figure 2B).…”
Section: Construction Of Snp Associated Regulatory Network Of Immune ...supporting
confidence: 75%
“…C–C Motif Chemokine Receptor 5 ( CCR5 ) was one of the downstream TGs in this regulatory network, and it encoded a protein on the surface of white blood cells that are involved in the immune system (Jiao et al 2019 ). We found that two TGs ( CCR5 and C-X-C Motif Chemokine Receptor 6 ( CXCR6 )) of the 15 immune TGs were also differentially expressed in blood samples of fatal COVID-19 patients (Wargodsky et al 2022 ) ( ), which proved that our reconstructed regulatory networks of immune cells were significantly associated with severity of COVID-19. In the COVID-19 severity-associated regulatory network in epithelium cells, there were 16 TFs, 24 REs, and 10 TGs that were associated with 42 SNPs (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…This includes an imbalanced innate host response to the SARS-CoV-2 with an aberrant activation of PMNs ( 23 ), and with unusually high release of pro-inflammatory cytokines ( 24 ). A recently reported comparison of circulatory levels of neutrophils secretory proteins showed that defensin DEFA1 level is higher in severe than in mild COVID patients ( 25 , 26 ). Similar data were published for the antimicrobial peptide LL-37 ( 26 ).…”
Section: Introductionmentioning
confidence: 97%
“…A recently reported comparison of circulatory levels of neutrophils secretory proteins showed that defensin DEFA1 level is higher in severe than in mild COVID patients ( 25 , 26 ). Similar data were published for the antimicrobial peptide LL-37 ( 26 ).…”
Section: Introductionmentioning
confidence: 97%